Evaluation of booster additive with different DOC body weight on Broiler production performance in closed house - Muharlien, Muharlien; Sudjarwo, Edhy; Yulianti, Dyah Lestari; Prayogi, Heni Setyo (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
This experiment was carried out in a 7,500 m2 poultry closed house located between the geographical coordinates 7°21ʹ-7°31ʹ south latitude and 110°10ʹ-111°31ʹ    west longitude and an average altitute of 654 m, from July to August 2020. The chickens were placed in 24 pens measuring 1 m2 each at stocking density of 4 chickens m-2. This study aimed at evaluating the effect of three initial weight (chick weight on first day of experiment) and two types of mixed feed on broiler performance. A total 96 day old chicks strain CP 707 derived from the same flock of breeders, was distributed in completely randomized experimental design with 3 (initial weight) by two type of mixed feed five repliated per treatment. The feed was complete feed produced by PT. Charoen Pokphand Indonesia Tbk. Complete feed was given based on the maintenance phase, include BR0 (1-7 days old), BR1 (8-21 days), and BR2 (>21 days). The booster additive was a commercial product. Initial weights were classified as light (37-41 g), medium (42-46 g) and heavy (>47 g), whereas mixed feed (with and without additive booster) were used as daily chicken feed.  Data were analyzed by ANOVA and means were compared by Tukey’s test at 95% confidence level. Initial weight and types of mixed feed have no effect on feed consumption, body weight gain, feed conversion, dan production index.